The Open Mind: War Crimes: How Much Do We Care About Them?
Host Richard D. Heffner interviews Aryeh Neier, President of the Soros Foundation and the Open Society Institute, on his book entitled “War Crimes: Brutality, Genocide, Terror and the Struggle for Justice.”